Comunidades de briófitos reofílicos en un caño de montaña, en San Francisco, Cundinamarca, Colombia - Linares Castillo Edgar Leonardo; Churchill Steven P. (Caldasia)
The rheophilic bryophyte vegetation of a montan e stream between 2450-2650 m alt, near San Francisco, in the northwest of Cundinamarca, on the western slope of the Colombian Cordillera Oriental, was studied following the Zürich-Montpellier approach. Recognized were: 1) community of Thamnobryum fasciculatum and Monoelea gottschei. under foresto and 2) community of Brachythecium plumosum and Platyhypnidium aquaticum. outside the forest. The structure, floristic composition and ecological aspects were considered. Se estudió la vegetación de briófitos reofílicos en un caño de montaña, en el gradiente altitudinal entre 2450 y 2650 m. Se hallaron dos comunidades: una comunidad de Thamnobryum fasciculatum y Monoelea gottschei propia del interior del bosque y otra comunidad de Brachythecium plumosum y Platyhypnidium aquaticum de los potreros. Se registró la estructura, composición florística, los rasgos ecológicos y la distribución de las comunidades.